1998
DOI: 10.1002/(sici)1098-2302(199803)32:2<69::aid-dev1>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of long‐term memory over the first year‐and‐a‐half of life

Abstract: This research documents the development of long-term memory in human infants from 2 months through the end of the first year-and-a-half of life. In the initial study phase, we trained 6- to 18-month-old human infants in an operant task and tested them after increasing delays until they exhibited no retention for 2 successive weeks. In the second phase, their data were combined with data previously obtained from 2- to 6-month-olds in an equivalent task. The resulting function revealed that the duration of reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 41 publications
(67 reference statements)
4
40
0
Order By: Relevance
“…We found that 90% of infants responded at least 50% above baseline for at least 2 consecutive minutes (Hartshorn et al, 1998), and all exceeded 25% of baseline in the final 2 min. Only 2 infants who did not meet the criterion met the Hartshorn et al (1998) criterion (50% above baseline in Minutes 2-3 or Minutes 3-4, respectively), but they responded below baseline during 3 of the 4 remaining minutes.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…We found that 90% of infants responded at least 50% above baseline for at least 2 consecutive minutes (Hartshorn et al, 1998), and all exceeded 25% of baseline in the final 2 min. Only 2 infants who did not meet the criterion met the Hartshorn et al (1998) criterion (50% above baseline in Minutes 2-3 or Minutes 3-4, respectively), but they responded below baseline during 3 of the 4 remaining minutes.…”
Section: Resultssupporting
confidence: 67%
“…Because the criterion assessed minimum response levels, maximum (peak) and final learning levels of infants in this paradigm were typically greater. Infants who met the minimum criterion were also likely to meet a commonly accepted learning criterion of contingency mastery, that is, 1.5 × baseline for 2 consecutive minutes (Hartshorn et al, 1998).Frustration measures-The two aspects of the frustration response assessed were changes in arm response and changes in facial expression. Both were examined because the different frustration conditions might have affected the relation between arm responses and expressions.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Using these paradigms this team of researchers found that in the first year of life there is a dramatic increase in memory retention (see Hartshorn et al, 1998a). In addition, the ability to recall an event from a related ' prime' or associated contingency or cue increases as a function not only of age, but also of the duration of the prime (Hsu, Rovee-Collier, Hill, Grodkiewicz & Joh, 2005): Hsu et al (2005) found that the duration of a prime needed to reactivate a memory decreased logarithmically with age.…”
Section: Recognizing Familiar Wordsmentioning
confidence: 60%